Rekayasa dan Pembuatan Mesin Pencacah Sampah Organik Dual Function Untuk Mendukung Sistem Konversi Limbah Organik menjadi Biogas - Suparni Setyowati Rahayu; Gatot Santoso; Samuel Kristiyana; Anak Agung Putu Susastriawan; Satriawan Dini Hariyanto; Dewi Wahyuningtyas (Jurnal Rekayasa Mesin, 2023)
In recent years, domestic carbage become a serious problem since not all waste is managed properly. The organic waste has a potential as a feedstock for biogas production. Before the fermentation process of biogas production, it is necessary to enumerate organic waste with the help of a multi-function chopper. In the present work, dual function machine (chopping and milling process) is designed and fabricated. The machine is driven with a 5.5 HP gasoline engine with a two-way transmission system connecting to each process. The first line transmission system on the chopping with a pulley size of 2 inch diameter, two grooves mounted on the motor and a 3 inch pulley mounted on the chopper axis with a rotation speed of 2400 rpm. The second line transmission system on the milling uses a 12 inch diameter pulley with a rotation of 600 rpm. The test results show that the capacity of the machine was 60 kg/h with 1 cm chopping size.